Making (small) firms happy: The heterogeneous effect of trade facilitation measures - Lionel Fontagné; Gianluca Orefice; Roberta Piermartini (World Trade Organization (WTO), 2016)
This paper considers the asymmetric effect of Trade Facilitation Agreement (TFA) policies on heterogeneous exporters, based on matching a detailed panel of French firm exports to a new database of Trade Facilita- tion Indicators (TFIs) released recently by the Organisation for Economic Cooperation and Development (OECD). We analyze the effect of these TFIs on three trade-related outcomes: (i) exported value (firm intensive margin), (ii) number of products exported (product extensive margin) and (iii) average export value per product exported (product intensive margin). We find strong evidence of a heterogeneous effect of trade facilitation across firm size. While better information availability, advance ruling and appeal procedures mainly benefit small firms, the simplification of documents and automation tend to favor large firms' trade. This is coherent with the idea that while some elements of the TFA simply reduce the fixed cost of exporting (favoring small firms in particular), other chapters in the TFA reduce the scope for corruption at borders, making large firms less reluctant to serve corrupt countries.
Keywords: F13; F14; 330; Trade Facilitation; Heterogeneous Firms; Extensive Margin; Intensive Margin